2006
DOI: 10.1510/icvts.2006.139436
|View full text |Cite
|
Sign up to set email alerts
|

The short-term efficacy of fibrin glue combined with absorptive sheet material in visceral pleural defect repair

Abstract: Tissue sealants can prevent the occurrence of pulmonary air leakage, although few studies have evaluated the seal-breaking pressure properties of the various methods. We developed a new method for repairing visceral pleural defects which combines fibrin glue with a sheet material. We used an animal model to compare its efficacy with that of three current techniques up to 24 h after application. Under thoracotomy, 5 x 20 mm visceral pleural defects with a depth of 3 mm were made in beagles. The defects in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…Furthermore, it is sometimes diffi cult to suture or plicate a large defect or a lung weakened by emphysema, thereby leaving overlapping as the most appropriate and simple method to repair the defect. 3 Fibrin glue-coated collagen fl eece (TachoComb; CSL Behring, Tokyo, Japan), is a stretchable and adhesive tissue sealant that can be used to repair pleural defects and hemorrhage. Pressure is constantly applied to a pleural defect by ventilation; the collapse and infl ation of the lung changes the shape and size of the defect.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is sometimes diffi cult to suture or plicate a large defect or a lung weakened by emphysema, thereby leaving overlapping as the most appropriate and simple method to repair the defect. 3 Fibrin glue-coated collagen fl eece (TachoComb; CSL Behring, Tokyo, Japan), is a stretchable and adhesive tissue sealant that can be used to repair pleural defects and hemorrhage. Pressure is constantly applied to a pleural defect by ventilation; the collapse and infl ation of the lung changes the shape and size of the defect.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, they found that the use of PGA mesh in combination with fibrin glue, with the use of rubbing method, could achieve the highest sealing potential in an animal model [16,17]. Currently, PGA mesh and fibrin glue are commonly used not only in respiratory surgery but also in neurosurgery [18] and general surgery [19] in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The application of fi brin glue is one of the most frequent modalities and it is widely used, 2-6 whereas industrial materials have also been developed and are often combined with fi brin glue. [7][8][9][10][11] Polyglycolic acid felt is used for its effectiveness and safety. 11,12 A recent report noted its utility for hemostasis in a lacerated liver, and the application of PGA may expand in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Polyglycolic acid felt is used for its effectiveness and safety. 11,12 A recent report noted its utility for hemostasis in a lacerated liver, and the application of PGA may expand in the future. 13 Although PGA felt may cause postoperative infection, or empyema as organ/space SSI, there was no signifi cant difference in the incidence and type of SSI between the PGA(+) and PGA(−) group in the current study (Table 1).…”
Section: Discussionmentioning
confidence: 99%